A3_4 King of the Swingers - Cooper, Dan; Reiness, Sean; Sidhu, Manika; Watson, Charlie (Physics Special Topics, 2017)
The idea of swinging on a vine as a means of travel within a jungle is one that has been used in a variety of contexts; while the physical act may be difficult to do, modelling the action and calculating some value for the average horizontal ground velocity can be done with relative ease. Within films and books it has been used for many years; the chase scene from the movie 'Indiana Jones and the Kingdom of the Crystal Skull' is one such film. From investigating this scene the average horizontal ground velocity of Shia la Beouf is found to be 15.3 ms^-1.